Controllable preparation of bioactive open porous microspheres for tissue engineering. Issue 34 (12th August 2022) - Lin, Anqi; Liu, Shengyang; Xiao, Lan; Fu, Yingying; Liu, Changsheng; Li, Yulin
Abstract : PLGA open porous microspheres (OPMs) with uniform particle size, controllable pore size, good biocompatibility and high cell loading capacity were successfully prepared using a gas-assisted-emulsion and surface-alkalization-treatment technology. Abstract : Biodegradable microspheres have been widely applied as cell carriers for tissue engineering and regenerative medicine. However, most cell carriers only have a simple planar structure and show poor biological activity and cell adherence, resulting in low cell density and unfavorable application effect. How to develop size-controllable microspheres with an open-porous structure remains a challenge, and is a key factor to extend their employment as cell/drug delivery vehicles to boost regeneration of tissues ( e.g., bone). Herein, well-defined open porous microspheres of poly(lactic- co -glycolic acid) (PLGA with good biocompatibility approved by the Food and Drug Administration (FDA)) were developed by using a gas-assisted-emulsion and surface-alkalization-treatment technology (GEST). The gas-assisted-emulsion strategy enables the formation of microspheres with a large size of 200–300 μm, meanwhile, the microspheres have a large amount of micropores with diameter in the range of 10–60 μm. The following alkalization-treatment on the surface makes the microspheres form a good porous interconnectivity throughout both the surface and the interior of the microspheres. The good porous interconnectivity endows the microspheres with a highly open pore structure and a large specific surface area for nutrient exchange and cell attachment, thus promoting cell proliferation and nutrient transportation, promising their potential as an ideal cell carrier to increase cell density and bioactivity for cell therapy-based tissue engineering.